2019
DOI: 10.1111/acer.14197
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acute Motor Effects and Tolerance Following Self‐Administration of Alcohol and Edible ∆9‐Tetrahydrocannabinol in Adolescent Male Mice

Abstract: IIBackground: Cannabinoids and their principle psychoactive target, the cannabinoid type 1 receptor (CB1R), impact a number of alcohol-related properties, and although alcohol and cannabis are often co-used, particularly in adolescence, few animal models of this phenomenon exist. We modeled the couse of alcohol and Δ 9 -tetrahydrocannabinol (THC) in adolescent mice using ingestive methods popular during this developmental period in humans, namely binge-drinking and edible THC. With this model, we assessed leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
(101 reference statements)
0
1
0
1
Order By: Relevance
“…However, this does not preclude the possibility that higher doses of EtOH produce motor impairment. Indeed, impaired performance in the rotarod test occurs after administration of the higher doses of EtOH used in this study (Pandey, 2012;Smoker et al, 2019;Tornberg et al, 2007), which may contribute to the increased paw withdraw thresholds observed in both SNI and sham control animals following administration of the higher doses of EtOH. One challenge in interpreting DWB data in nerve injury models is determining whether the changes in weight bearing are observed due to the pain and hypersensitivity caused by the injury or other aspects of the injury, such as motor deficits (Sik Naa et al, 1996).…”
Section: Discussionmentioning
confidence: 87%
“…However, this does not preclude the possibility that higher doses of EtOH produce motor impairment. Indeed, impaired performance in the rotarod test occurs after administration of the higher doses of EtOH used in this study (Pandey, 2012;Smoker et al, 2019;Tornberg et al, 2007), which may contribute to the increased paw withdraw thresholds observed in both SNI and sham control animals following administration of the higher doses of EtOH. One challenge in interpreting DWB data in nerve injury models is determining whether the changes in weight bearing are observed due to the pain and hypersensitivity caused by the injury or other aspects of the injury, such as motor deficits (Sik Naa et al, 1996).…”
Section: Discussionmentioning
confidence: 87%
“…Ebenfalls unbeeinträchtigt von einer Behandlung mit THC blieb auch die motorische Ausdauer, Koordination und das Lernverhalten der weiblichen 5XFAD-Mäuse im Rotarod-Test. Untersuchte man die motorische Aktivität von C57BL/6J-Mäusen im eigenen Käfig, zeigte sich nach direkter THC-Einnahme eine signifikante Abnahme der motorischen Aktivität(Smoker et al 2019). Da sich jedoch vor allem in Angsttests eine signifikant geringer zurückgelegte Distanz zeigte, sollte dies unbedingt im Zusammenhang mit einer gesteigerten Ängstlichkeit interpretiert werden(Ennaceur 2014;Lutz et al 2015).…”
unclassified